Unjuk Kerja Strategi Global Layering Pada Jaringan GSM 900/1800 - Nur Aziz Salim (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2014)
Recently, the development of telecommunication is getting faster following the high amount of its users and the highgrade quality of telecommunication networks need. Due to this reason, it is highly needed an optimizing activity to keep and improve the performance telecommunication network. The optimizing is done for maintaining and improving the performance of 2G GSM network. In this paper, the performances that will be analyzed are accessibility, retain ability, and integrity which will be represented by 5 KPIs (Key Performance Indicator).In this paper, author is aiming to discover the extend of the influence of global layering strategy implementation on 2G GSM 900 and GSM 1800 to the GSM network performance. The optimizing strategy being used in this research is global layering strategy; the implementation is by engage all cells in the same range and by prioritizing the traffic network of GSM 1800 to GSM 900 network either in the idle or dedicated condition. The result of strategy global layering show that all KPI improved except KPI TBF establishment success rate. This degradation caused by unbalance traffic between GSM 900 and GSM 1800.